Metabolic Control of Cardiomyocyte Cell Cycle - Ivan Menendez-Montes; Daniel J. Garry; Jianyi (Jay) Zhang; Hesham A. Sadek (Methodist DeBakey Cardiovascular Journal)
Current therapies for heart failure aim to prevent the deleterious remodeling that occurs after MI injury, but currently no therapies are available to replace lost cardiomyocytes. Several organisms now being studied are capable of regenerating their myocardium by the proliferation of existing cardiomyocytes. In this review, we summarize the main metabolic pathways of the mammalian heart and how modulation of these metabolic pathways through genetic and pharmacological approaches influences cardiomyocyte proliferation and heart regeneration.